Cytological Diagnosis of Follicular Patterned Lesion of Thyroid Nodule and its Follow-up Histopathology - Ali, Md Tokres; Roshed, Md Mahabubur; Ali, Mohammad; Jahan, Mahmuda; Akhter, Most Dalia (Mediscope, 2023)
The follicular patterned lesion of thyroid nodules is an exciting topic because it is not clear whether the lesion is benign or malignant. It comprises hyperplastic/adenomatoid nodules, follicular adenoma, follicular carcinoma and follicular variant of papillary carcinoma. The cytological diagnosis of atypia of undetermined significance/Follicular lesion of undetermined significance, follicular neoplasm/suspicious for follicular neoplasm and suspicious for malignancy remains controversial in terms of management. The study aimed to examine the extent of invasion of malignant lesions in follow-up histopathology diagnosed as undetermined lesions cytologically. A total of 256 cases were included in this study; among these, 199 cases were benign lesions, 15 cases were non-diagnostic and 42 cases were diagnosed either of uncertainty for malignancy with cellular atypia or malignancy. Subsequent follow-up resection and histopathology were done with 48 cases (18.75%), which comprises 1 non-diagnostic, 10 benign lesions, 21 atypia of undetermined significance/Follicular lesion of undetermined significance, 7 Follicular neoplasm/Suspicious for a follicular neoplasm, 5 suspicious for malignancy and 4 malignancies. Also, 6 Follicular variant of papillary thyroid carcinoma, 6 classic papillary carcinoma, 5 follicular carcinoma and 1 anaplastic carcinoma were diagnosed in follow-up resection histopathology of 48 cases. Thirty eight cases were of undetermined significance of malignancy with cytological features of the follicular lesion. Four Follicular variant of papillary thyroid carcinoma, 2 follicular carcinoma and 1 papillary carcinoma were diagnosed in 21 resected cases cytologically reported as Atypia of undetermined significance/Follicular lesion of undetermined significance with malignancy risk of 33.33%. Three malignancies in follicular neoplasm/suspicious for a follicular neoplasm with a risk of 42.85% and 4 malignancies in suspicious malignancy group with a risk of 80% were found. The average risk of malignancy of these three undetermined categories was reduced to 24.24% from 42.42% upon reclassification of the Follicular variant of papillary thyroid carcinoma. All the Follicular variants of papillary thyroid carcinoma diagnosed by histopathology were non-invasive regarding lymph node involvement and microvascular or capsular invasion. Mediscope 2023;10(2): 68-77